The Role of Social Institutions in National Character Education - Naffa Asti Aprilia; Sruni Rama Lestari; Noviyanti, Silvina; Chan, Faisal (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study aims to analyze the role of social institutions in shaping and strengthening national character education in Indonesia. Using a qualitative literature study method, this research examines written sources such as journals, books, and scientific articles to synthesize findings related to social institutions’ influence on character education. The study reveals that social institutions families, schools, religious institutions, and community groups play a crucial role in fostering values like honesty, discipline, tolerance, and responsibility. The research's novelty lies in its holistic approach to integrating diverse social, economic, and cultural dimensions, addressing gaps in character education implementation, especially between urban and rural areas. This study contributes to the discourse by highlighting the need for synergistic collaboration among social institutions to overcome challenges posed by globalization and technological change. The findings have significant implications for policymakers in designing integrative education strategies that enhance moral and social integrity while ensuring equal access to quality character education across regions.